Global and China trends and forecasts of disease burden for female lung Cancer from 1990 to 2021: a study based on the global burden of disease 2021 database - Bilu Li; Yuyan Wu; Yanhong Zhang; Chengyun Hu; Xue Li; Shanshan Luo; Chenyu Sun; Iyad Yousef; Yefei Wang; Chaoliang Tang (Journal of Cancer Research and Clinical Oncology)
Abstract Background In recent years, due to various risk factors, the incidence, prevalence, and mortality rates of female lung cancer have been increasing in both China and globally. This has become a significant public health challenge worldwide. Lung cancer not only poses a severe threat to women’s health but also places a heavy burden on families and society. Objective To conduct an in-depth analysis of the trends in disease burden for female lung cancer in China and globally from 1990 to 2021 and to forecast the next 15 years (2022–2037). The aim is to provide a reliable theoretical basis and reference value for clinical research and practice in female lung cancer and offer guidance for resource allocation and policy-making in society. Methods Based on the Global Burden of Disease (GBD) 2021 database, we analyzed the incidence, prevalence, mortality, and disability-adjusted life years (DALYs) of lung cancer in China and globally from 1990 to 2021. These metrics were stratified by gender (BOTH, MALE, FEMALE), and the average annual percentage change (AAPC) was calculated for each metric over this period. The JOINPOINT regression model was used to analyze the trends in female lung cancer in China and globally from 1990 to 2021. The ARIMA model was applied to forecast the changes in age-standardized incidence rates (ASIR) and age-standardized mortality rates (ASDR) for the next fifteen years (2022–2037) for female lung cancer in China and globally. Results The results indicate an upward trend in incidence, prevalence, mortality, and DALYs for lung cancer in China. Globally, the prevalence of lung cancer showed an increasing trend, while the incidence, mortality, and DALYs demonstrated a declining trend. Both in China and globally, the incidence, prevalence, mortality, and DALY trends for female lung cancer were higher than those for males. From 1990 to 2021, the incidence, prevalence, mortality, and DALYs of female lung cancer in China exhibited an upward trend, with AAPC growth rates of 1.151%, 2.086%, 0.508%, and 0.210%, respectively. Similarly, globally, the incidence, prevalence, and mortality of female lung cancer also showed an upward trend, with growth rates of 0.576%, 1.123%, and 0.276%, respectively, while DALYs showed a slight decline with an AAPC of -0.029%. Conclusion Although the overall disease burden of female lung cancer is not as high as that of males, the growth rate for female lung cancer is significantly higher than that for males both in China and globally. The overall disease burden and the growth rates of incidence and prevalence of female lung cancer in China are higher than the global average.